Incidence of the lean philosophy construction in the productivity and analysis of processes in internal finishes in masonry living quarters in the construction projects: case-residential complex Callejas-Cucuta-Colombia (2018)
The technical supervision in the construction projects is of special importance for the correct execution of the activities, its objective is to reduce the errors that are incurred when carrying out the processes inherent to its development. The finishes, as a final stage in the construction of homes, generate visual appeal to customers by encouraging their option of purchase. However, the costs contemplated in this stage are important in the budget. Defining an efficient work method helps improve the completion time of the activity by promoting compliance with the schedule stipulated for the project, together with the improvement of profitability for the contractor. The present work applies some tools of the Lean Construction philosophy of the two methods implemented in the application of the coating and detailing or final finishing for houses built in masonry, through continuous observation, using the balance sheet tools, the Last Planner system with the weekly schedule and lines of balance for the programming of activities. From these measurements, time-operator relationships were obtained, which sought to identify productive, contributory and noncontributory activities that affect productivity in the development of the project, reaching conclusions that maximize productivity, reducing activities that do not generate value to the Project.